Probing Poincaré violation - Gupta, Rick; Jaeckel, Joerg; Spannowsky, Michael (Journal of high energy physics, 2023)
Time and space translation invariance, giving rise to energy and momentum conservation, are not only amongst the most fundamental but also the most generally accepted symmetry assumptions in physics. It is nevertheless prudent to put such assumptions to experimental and observational tests. In this note, we take the first step in this direction, specifying a simple periodic time dependence that violates time translation invariance in QED, and setting phenomenological constraints on it. In addition to observational and experimental constraints on time varying couplings, we focus on probes of violation of energy conservation such as spontaneous production of photon and electron pairs and the e → eγ process. We discuss similarities and differences to the discussion of time varying fundamental constants and to the case of a light bosonic dark matter field that usually also causes oscillating effects.